Kajian Tingkat Kebisingan Pertambangan yang Diterima pemukiman sekitar Tambang di Kabupaten Magelang, Jawa Tengah - Wijaya, Nely (ReTII, 2019)
Mining Activities are activities that are dense with activities that can cause noise and disturbs the urban environment around the location of the mining activity. The Ministry of the Environment has a high priority regarding the sound environment in the environment, especially the social environment. Using the survey method based on the Minister of the Environment Decree No. 48 of 1996 for measuring the level of approval in the Mining and Settlement area and collecting security sources, bases of mining site layout and settlements. Vegetation in the area around the mine site has a low density. The activities of the mechanization of the two crusher units contributed the most assistance for 24 hours with the types of continuous and intermittent contributions while the drilling activities of fisheries which have a higher level of importance and cheaper contributions including continuous types. But when the production hours reach 07.00 until 21.45 WIB. Vegetation rigidity that need to be held to save those received in settlements.